Dithienopyrrole‐/Benzodithiophene‐Based Donor–Acceptor Polymers for Memristor. Issue 9 (20th June 2014) - Wang, Cheng; Liu, Gang; Chen, Yu; Liu, Shanshan; Chen, Qibin; Li, Runwei; Zhang, Bin
Abstract Two new donor (D)–acceptor (A) copolymers, poly({4, 4′‐[4, 4′‐(9H‐fluorene‐9, 9‐diyl)bis(4, 1‐phenylene)]bis(oxy)diphthalonitrile}‐alt‐[dithieno [3, 2‐b:2′, 3′‐d]pyrrole]) (P1) and poly({4, 4′‐[4, 4′‐(9H‐fluorene‐9, 9‐diyl)bis(4, 1‐phenylene)]bis(oxy)diphthalonitrile}‐alt‐([1, 2‐b:4, 5‐b′]dithiophene)) (P2), have been designed and synthesized by the Stille coupling reaction. The dipole moment of P1 (10.71 Debye) is larger than that of P2 (6.59 Debye). A strong dipole moment helps to sustain the conductive charge‐transfer state. To evaluate the nonvolatile memristive performance of P1 and P2, the corresponding memory device can be fabricated with the configuration of platinum (50 nm)/polymer (100 nm)/platinum (150 nm)/silicon. In contrast with the P2‐based device with almost negligible switching and memristive behavior, the P1‐based memristor exhibits a maximum ILRS/IHRS ratio of about 10 (ILRS and IHRS are the current values in the low‐resistance state (LRS) and high‐resistance state (HRS), respectively) at ±2.0 V. Distinguishable from the bistable resistive switching, showing abrupt resistance or conductance jumps, the electrical transition observed in the memristor demonstrates a smoother tuning of the sample conductance during the voltage sweeping processes. In addition, changes in the surface morphology of P1 and P2 are also observed under an applied bias voltage of 100 mV.